Application of initiation catalyst in preparation of thermal expansion microspheres
By using initiating catalysts made of mixing inorganic oxides and organic ammonia in the preparation of thermal expansion microspheres, combined with specific formulation and reaction conditions, the poor performance and industrial production problems of thermal expansion microspheres in the prior art have been solved, and efficient and regular microsphere preparation and production efficiency have been achieved.
Patent Information
- Application Number
- CN202411881560.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
AI Technical Summary
It is difficult to synthesize thermal expansion microspheres with uniform particle size distribution, regular morphology, high foaming ratio and superior foaming performance in the prior art, and industrial production faces problems such as complex process control and high equipment requirements.
The initiation catalyst is composed of mixing inorganic oxides and organic ammonia. The thermally expanded microspheres are prepared by adding initiation catalysts during the polymerization reaction, and combined with specific aqueous and oil-phase materials preparation, homogeneous stirring and polymerization reaction conditions.
It achieves fast reaction speed, short preparation cycle, comparable performance and yield of the prepared thermally expanded microspheres, improve production efficiency, and meet the conditions for industrialized large-scale production.
Smart Images

Figure CN119708600A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to application of an initiating catalyst in the preparation of thermal expansion microspheres. Background Art
[0002] Thermal expansion microspheres are microspheres with volatile low-boiling-point hydrocarbon organic matter encapsulated in a thermoplastic resin shell. The particle size is between 5 and 75 microns. When the microspheres are heated, the thermoplastic shell softens, and the low-boiling-point organic matter in the microspheres vaporizes, causing the internal pressure to increase. The gas expands the shell, and the volume of the foamed microspheres can expand to dozens or even hundreds of times. Therefore, it is used as a foaming agent (closed-cell type) and lightweight filler in different fields and scenarios, and its application range in lightweight, heat insulation, sound insulation, shock absorption, patterning, three-dimensional and other fields is becoming wider and wider.
[0003] In terms of basic research, many scholars have conducted a lot of fruitful research on the design of polymer shell wall composition of thermal expansion microspheres. For example, Jonsson et al. prepared heat-resistant high-temperature thermal expansion microspheres with acrylonitrile (AN) and methacrylonitrile (MAN) as the main monomers, focusing on the influence of crosslinker type and dosage on the performance of thermal expansion microbubbles. Yasuhiro et al. prepared thermal expansion microspheres by adding different third monomers to the AN / MAN polymerization system, focusing on the influence of crosslinker type and dosage on the foaming temperature and foaming performance of thermal expansion microspheres. Xie Guiming et al. prepared thermal expansion polymer microspheres by suspension polymerization with vinylidene chloride, AN, and methyl methacrylate (MMA) as comonomers, focusing on the influence of aqueous phase additives such as sodium chloride, citric acid and potassium dichromate on the structure and expansion performance of polymer microspheres. Liu Feng's research group used AN and MMA as the main monomers, and synthesized high-temperature thermal expansion microspheres U3-151 with excellent foaming performance by adding polar comonomers such as methacrylic acid (MAA) and NN-dimethylacrylamide (DMAA).
[0004] In terms of applied research, researchers in the industry have carried out a lot of work. For example, Ahmad et al. added thermoplastic heat-expandable microspheres to vinyl plastic substrates to improve the elasticity of the material. Such materials have application value in many fields such as automotive bottom coatings, gaskets, and sports goods. Whinnery et al. used commercially available Expancel heat-expandable microspheres as heating to prepare a series of materials with different densities and mechanical foams, providing a new method. Wu Minghua et al. mixed heat-expandable microspheres into printing slurry, printed them on fabrics, and used them to print fabrics, increasing the three-dimensional effect while maintaining the original effect of the pattern, thereby improving the quality of the product.
[0005] Although many domestic scholars have participated in the research of heat-expandable microspheres, from the perspective of industrial production, it is difficult to synthesize heat-expandable microspheres with uniform particle size distribution, regular morphology, high foaming ratio and excellent foam stability due to the complex process control and high requirements for production equipment in the production of heat-expandable microspheres, as well as the many factors that affect the structure and performance of microspheres. There are not many domestic companies that can produce heat-expandable microspheres on a large scale, and the production capacity is insufficient. The preparation technology of heat-expandable microspheres still needs to be further improved. Summary of the invention
[0006] Aiming at the deficiencies of the prior art, the present invention proposes an application of an initiating catalyst in the preparation of thermal expansion microspheres.
[0007] This is achieved specifically through the following technical solutions:
[0008] The invention discloses an application of an initiating catalyst in the preparation of heat-expandable microspheres. The initiating catalyst is composed of a mixture of one or two inorganic oxides and organic ammonia. The initiating catalyst is uniformly mixed at a mass ratio of 2 to 6:1 between the inorganic oxide and the organic ammonia. When used, 30% ethanol is added at a mass ratio of 1:100 and then completely dissolved before use.
[0009] Furthermore, the inorganic oxide is composed of one or two of potassium persulfate, sodium persulfate, ammonium persulfate, and hydrogen peroxide, and the organic ammonia is one of ethylenediamine, triethanolamine, and monoethanolamine.
[0010] The method for preparing the heat-expandable microspheres comprises the following steps:
[0011] (1) Preparation of aqueous phase material: 2 In an atmosphere, deionized water, sodium nitrite, polyvinyl pyrrolidone, and sodium chloride are mixed and completely dissolved, and hydrochloric acid, ethanol, and colloidal silica are added, and stirred to be evenly dispersed to obtain a uniform emulsion with a pH value of 5.5-7.0;
[0012] Furthermore, in terms of mass ratio, the ratio of ionized water: sodium nitrite: polyvinyl pyrrolidone: sodium chloride: hydrochloric acid: ethanol: colloidal silicon is:
[0013] 65~74:0.15~0.2:0.15~0.2:20~25:0.04~0.08:1.5~2.5:7.5~9.0;
[0014] (2) Preparation of oil phase material: N 2 In the atmosphere, add acrylonitrile, methyl methacrylate, methacrylonitrile, methacrylic acid, glycidyl methacrylate monomers into a beaker in sequence, then add a crosslinking agent and an initiator, stir to completely dissolve them, then add a foaming agent, stir to evenly disperse them, and set aside; the process temperature is controlled below 20°C;
[0015] Furthermore, by mass ratio, the ratio of acrylonitrile: methyl methacrylate: methacrylonitrile: methacrylic acid: glycidyl methacrylate is: 1:0.6:0.8:0.6
[0016] (3) Homogenization: First use N 2 Replace the homogenizing kettle, then add the prepared water phase material and oil phase material into the homogenizing kettle at a volume ratio of 0.79:0.21, then add the foaming agent into the kettle, close the valve, and use a 3000rpm high-speed stirrer for homogenization and dispersion. The process temperature is controlled at 5-35°C, and the homogenization time is 0.5 hours;
[0017] (4) Polymerization reaction: First use N 2 The polymerization reactor is replaced, and the materials in the homogenization reactor are pressed into the polymerization reactor with nitrogen. After the materials are transferred, the reactor pressure is continuously increased to 0.5 MPa with nitrogen, the valve is closed, the stirring rate is controlled at 120 rpm, the temperature is gradually raised to 60° C. within 2 hours, and then the reaction is maintained at 60° C. and 0.5 MPa until half of the total reaction time, an initiating catalyst is added, the reaction is continued until the reaction is completed, the temperature is lowered to 40° C., the pressure is released, and the material is discharged; filtering, washing with deionized water, and air drying at 60° C. until the moisture content is less than 2.5%, to obtain a finished product of heat-expandable microspheres;
[0018] (5) Recovery of sodium chloride: Activated carbon is added to the filtered mother liquor for decolorization. After filtration, the filtrate is concentrated, crystallized, and filtered to obtain recovered salt (sodium chloride). The recovered sodium chloride is returned to the aqueous phase material for continued use.
[0019] Furthermore, the crosslinking agent is trimethylolpropane trimethacrylate, accounting for 2.3% of the total weight of the monomers, and the initiator is azobisisobutyronitrile, accounting for 1.3% of the total weight of the monomers. The average particle size of the obtained heat-expandable microspheres is 12-35 μm, the moisture content is <2.5%, and the foaming ratio is >28.
[0020] Beneficial effects:
[0021] The invention adopts the technology of using AIBN+initiator in combination, and adopts the method of adding initiator in the polymerization reaction to prepare the heat-expandable microspheres, which has the excellent effect of fast reaction speed and short preparation cycle (time can be shortened by 45%), and the performance and yield of the prepared heat-expandable microspheres are equivalent, which can effectively improve the production efficiency of the heat-expandable microspheres. The invention uses azobisisobutyronitrile (AIBN) as an initiator and adds it to the oil phase material, and then mixes it with the water phase material. After high-speed stirring and homogenization, the monomer dissolved with the initiator forms a stable suspension in the form of small liquid droplets in water and then performs polymerization reaction. When the concentration of azobisisobutyronitrile (AIBN) gradually decreases and the reaction speed decreases after the polymerization reaction is carried out for a certain period of time, the initiator is added to accelerate the decomposition rate of azobisisobutyronitrile (AIBN) under the action of the catalyst, thereby accelerating the polymerization reaction speed and reducing the overall reaction time.
[0022] In particular, by adding an initiator catalyst halfway through the polymerization reaction, the decomposition rate of ANBI is accelerated, the speed of the late polymerization reaction is increased, and the reaction is shortened to achieve good results. The raw materials in the determined process are easy to obtain, the reaction is mild, and the temperature and pressure fluctuations during the preparation process are not large and are completely controllable. Verification of multiple batches has shown that the heat-expandable microspheres prepared by this process have small fluctuations in yield and product performance between each batch. The product has been tested through application proofing, and its performance has reached the level of the best similar products currently available on the market. The process has the conditions for industrial large-scale production transformation. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the particle size distribution diagram of the 22nd batch of samples;
[0024] Figure 2 This is a TM micrograph of the 22nd batch of samples;
[0025] Figure 3 This is a photo of the 22nd batch of samples, 1 ml of microsphere product, after heating and foaming;
[0026] Figure 4 This is a comparison report between the 20th, 21st and 22nd batches of samples and the better domestic similar products. DETAILED DESCRIPTION
[0027] The specific embodiments of the present invention are further described in detail below, but the present invention is not limited to these embodiments, and any improvement or substitution based on the basic spirit of the present embodiment still falls within the scope of protection required by the claims of the present invention.
[0028] Example 1
[0029] A method for preparing heat-expandable microspheres comprises the following steps:
[0030] (1) Preparation of water phase and oil phase liquid
[0031] Before compounding, the compounding container was purged with nitrogen (purity greater than 99.9%).
[0032] Preparation of aqueous phase: add 210g of deionized water, 0.54g of sodium nitrite, 0.53g of polyvinyl pyrrolidone, and 67.5g of sodium chloride in a beaker, stir to completely dissolve, then add 0.15g of hydrochloric acid, 6.3g of ethanol and 25g of colloidal silica, stir to disperse evenly, and set aside;
[0033] Water phase feed table
[0034]
[0035]
[0036] Preparation of oil phase: Add 20.3g acrylonitrile, 12.3g methyl methacrylate, 11.3g methacrylonitrile, 1.2g glycidyl methacrylate, 15.8g methacrylic acid, 1.4g trimethylolpropane trimethacrylate and 0.8g azobisisobutyronitrile in a beaker in sequence, stir to completely dissolve, then add 3.3g isooctane and 15g isopentane, stir to evenly disperse, and set aside; control the process temperature below 20°C.
[0037] Oil phase feed table
[0038] Serial number Material Name Feeding amount / g 1 Acrylonitrile (AN) 20.3 2 Methyl Methacrylate (MMA) 12.3 3 Methacrylonitrile (MAN) 11.3 4 Glycidyl Methacrylate (GMA) 1.2 5 Methacrylic acid (MAA) 15.8 6 Trimethylolpropane trimethacrylate (TMPTA) 1.4 7 Azobisisobutyronitrile (AIBN) 0.8 8 Isooctane 3.3 9 Isopentane 15
[0039] (2) Homogeneous reaction
[0040] First adopt N 2 The homogenizer was replaced with air, and then the prepared water phase and oil phase materials were transferred into the homogenizer (the homogenizer design pressure was 1.6MPa), the homogenizer was sealed, the feeding valve was opened, 1g of isobutane gas was introduced, and the valve was closed after the addition. The stirring power supply was started, and the materials were stirred at a high speed of 3000rpm for 0.5 hours to obtain a uniformly suspended and dispersed stable liquid.
[0041] Homogenizing feeding table
[0042] Serial number Material Name Feeding amount / g 1 Aqueous phase materials 310 2 Oil phase materials 81.4 3 Isobutane 1.0
[0043] (3) Suspension polymerization
[0044] First use N 2The polymerization reactor is replaced with air, and then the materials in the homogenization reactor are pressed into the polymerization reactor with nitrogen. After the materials are transferred, the reactor is closed, and the pressure of the reactor is continuously increased to 0.5MPa with nitrogen, and the valve is closed. The temperature is started to be gradually increased to 60°C within 2 hours under the control of 120rpm, and then the reaction is continued at 60°C and 0.5MPa for 20 hours, and the reaction is completed. The temperature is lowered to below 40°C, the material is discharged after the pressure is released, vacuum filtered, the filter cake is washed with deionized water, and the solid wet product is obtained after drying, and the finished product of heat-expandable microspheres is obtained after air drying at 60°C until the moisture content is less than 2.5%.
[0045]
[0046] (4) Recovery of salt from mother liquor
[0047] The mother liquor collected by filtration is transferred to a decolorization reaction bottle, activated carbon is added and stirred for 1 hour for decolorization, filtered, the filtrate is concentrated under reduced pressure, the residual liquid is cooled and crystallized, and filtered to obtain white solid sodium chloride with a purity of >99%. The recovered sodium chloride can be reused for the configuration of aqueous phase materials. The concentrated and collected condensed water is mixed with wastewater such as washing water and disposed of together.
[0048] (5) Three waste treatment solutions
[0049] The salt recovery process is also a pretreatment process for wastewater with high salt content in the product preparation process. Condensed water and filtrate from crystallization filtration are collected during salt recovery distillation and can be mixed with washing water for washing filter cakes, washing water for cleaning reactors and other containers in the product preparation process, and then treated together (biochemically); activated carbon is filtered out through dehydration and sent for disposal as hazardous waste, and waste gas in the production process is collected through negative pressure and discharged after centralized treatment.
[0050] 1. Microsphere product performance test
[0051] To ensure the stability of the process, 25 batches of verification experiments were carried out according to the method of Example 1, and the following performance test methods and characterization methods were used for detection. The results are shown in Table 1. (1) Determination of average particle size and particle size distribution of microspheres
[0052] Weigh 1g of washed and dried microspheres, add about 30mL of deionized water, stir evenly and disperse by ultrasound for 3min; measure the average particle size and particle size distribution of the microspheres by laser particle size analyzer. D50 is the average particle size, indicating that the number of particles with a particle size greater than this value accounts for 50% of the total number. The dispersion of the particle size distribution is span, where (span = (D90-D10) / D50). The smaller the span, the narrower the particle size distribution range. Taking the test data of the 22nd batch of samples as an example, the particle size distribution is as follows Figure 1 shown.
[0053] (2) Observation of microsphere morphology
[0054] The microcapsules were smeared on a glass slide and placed under an optical microscope. The eyepiece and objective lens were adjusted to observe the morphology and surface structure of the microspheres and record the size range and distribution of the particle size. The TM micrograph of the 22nd batch of samples is shown in the figure. Figure 2 shown.
[0055] (3) Microsphere foaming performance test
[0056] Precision constant temperature control hot stage. Raise the temperature of the hot stage at a rate of 10℃ / min and take photos of the foaming process. According to the readings on the precision constant temperature control hot stage, record the initial expansion temperature and contraction temperature, and calculate the stable foaming temperature range based on this.
[0057] (4) Thermal expansion microsphere foaming effect test (measuring cylinder method):
[0058] First, prepare a certain number of heat-expandable microsphere samples and a large enough measuring cylinder. Accurately weigh a certain weight of heat-expandable microspheres and add them to the measuring cylinder, and record the volume V1 at this time; place the measuring cylinder in a constant temperature box or water bath, and gradually heat it to a preset temperature (usually the starting foaming temperature of the microspheres), and keep it for a certain time to ensure that the microspheres are fully foamed; after the heating is completed, take out the measuring cylinder, and after the microspheres cool to room temperature, measure and record the volume V2 at this time again. By comparing the volume changes before and after heating, that is, V2 / V1. The foaming multiple of the heat-expandable microspheres can be calculated. The larger the ratio, the better the foaming effect. The photo of the 22nd batch of samples 1ml microsphere product after heating and foaming is shown below Figure 3 shown.
[0059] (5) Sole proofing test:
[0060] Mix PVC resin powder, DOP, stabilizer and color powder in a certain proportion, then add 10 / 1000th of the above mixture into the heat-expandable microsphere sample and mix again (each test sample mixture is 2 kg, and the mixing is done by machine). Use a PVC blower to make sole proofs for the powder after two even mixtures. According to the process requirements, set the temperature of each section of the machine, and control the temperature at 160-195°C (starting temperature: 160°C and maximum temperature: 195°C). After the proofing is completed, the sole is cooled and the sample is taken out. Cut the sample in section, observe and compare its hardness, density, whiteness and other indicators. Compare the proofs of the 20th, 21st and 22nd batches of samples with those of similar domestic products. The test results are as follows: Figure 4 shown.
[0061] Table 1 Validation batch test data table
[0062]
[0063] Statistical analysis of test data shows that the process determined in this study has high repeatability and the performance fluctuation of the prepared products is small.
[0064] 2. Screening Experiment
[0065] 1. Effects of different dispersants on microsphere performance
[0066] The heat-expandable microspheres are prepared by suspension polymerization. During the polymerization reaction, it is necessary to prevent the polymer particles from sticking together. The main functions of the dispersant are: first, to reduce the surface tension of the dispersed phase, making it easier to disperse. Due to the reduction in surface tension, the stirring speed can be reduced to achieve the same emulsified dispersion effect, thereby saving energy, facilitating operation, and facilitating industrialization; second, to protect the dispersed droplets, reduce the chance of monomer particles re-merging in an isolated manner, and increase the stability of the droplets. Therefore, at the same stirring speed, different emulsifying dispersants will form different emulsion dispersion states, which directly affects the particle size of the microspheres. The study used MgO (nano), Mg (OH) 2 (Nano), water-soluble polymer polyvinyl alcohol (PVA), nano-SiO 2 , colloidal silica was used as a dispersant, and the amount added was 20% of the monomer amount (unless otherwise specified, X% represents the percentage relative to the monomer), and an experimental comparison was performed. The results are shown in Table 2.
[0067] Table 2 Test data of some validation batches
[0068]
[0069]
[0070] Experiments show that MgO (nano), Mg (OH) 2 The particle size of the microspheres prepared by (nano) is relatively large. The particle size of the microspheres prepared by polyvinyl alcohol (PVA) varies and there is adhesion. 2 The microspheres can meet the requirements, but the dispersion of microspheres prepared by colloidal silica is slightly wider, and the amount of colloidal silica can be less at the same quality. Therefore, colloidal silica is preferred as a dispersant and as a raw material for further experiments.
[0071] 2. Effect of different dispersant dosage on microsphere performance
[0072] Using colloidal silica as a dispersant, heat-expandable microspheres were prepared by adding different amounts of colloidal silica under the same other conditions. The particle size test results of the microspheres are shown in Table 3.
[0073] Table 3
[0074] Colloidal Silicon Amount Average particle size (μm) The dispersion is span 10% Colloidal Silicon 38.21 2.63 13% Colloidal Silicon 34.88 2.18 15% Colloidal Silicon 32.45 1.95 18% Colloidal Silicon 27.66 1.72 20% Colloidal Silicon 24.82 1.64 22% Colloidal Silicon 23.18 1.60 25% Colloidal Silicon 22.85 1.54
[0075] It can be seen from the experimental data that the amount of dispersant has an important influence on the particle size and distribution of thermal expansion microcapsules. When the amount of colloidal silica is less than 13%, the obtained microcapsule particle size is larger and the distribution is wider. After increasing the amount of colloidal silica, the average particle size of the microspheres gradually decreases and the distribution becomes narrower. After the amount of colloidal silica is greater than 20%, the particle size and distribution of the microspheres do not change significantly. This is related to the distribution of colloidal silica on the surface of liquid phase oil droplets. Sufficient colloidal silica can be closely arranged on the surface of oil droplets, and the oil droplets can maintain good stability during the reaction. Therefore, the particle size distribution of the obtained microcapsules is narrow. When the colloidal silica is insufficient, the stability of the oil droplets is poor, and different oil droplets will aggregate during the reaction, and the particle size and distribution of the obtained product are not ideal. Continuing to increase the amount of colloidal silica, the particle size and distribution do not change significantly, resulting in waste, so 15-20% of colloidal silica is a more appropriate amount.
[0076] 3. Effect of adding initiator catalyst A on the reaction and microsphere performance
[0077] Initiator is the main factor affecting the polymerization rate and degree of polymerization. Suspension polymerization is a bulk polymerization reaction that occurs in small droplets of monomers suspended in water. The initiator should preferably be an oil-soluble initiator and dissolved in the monomer and fully mixed to facilitate the reaction; and the thickness of the microsphere shell of the heat-expandable microspheres needs to be as uniform as possible, which requires that the polymerization rate cannot be too fast and the reaction needs to proceed smoothly. However, general initiators have a long half-life, and the reaction rate will gradually slow down as the concentration of the initiator decreases in the later stage, and the reaction usually takes a long time. In order to shorten the reaction time as much as possible, the experiment uses azobisisobutyronitrile AIBN as the initiator, reacts for a period of time under 0.4MPa and 60℃, and then adds initiator catalyst A (accounting for 5% of the amount of AIBN, dissolved in water and ethanol) to increase the reaction rate and shorten the overall reaction time. By comparing the yield and performance of the microspheres obtained at the same reaction time, its influence on the polymerization reaction is judged. The results are shown in Table 4.
[0078] Table 4
[0079]
[0080] From the experimental data, the performance and yield of the microspheres obtained when only the initiator AIBN was added for 12 hours of reaction were very different from those when AIBN2 + catalyst A was added, which shows that the addition of catalyst helps to improve the reaction speed in the later stage and can significantly shorten the reaction time. Moreover, the performance and yield of the prepared microsphere product are not much different from those when only the initiator AIBN is added for 24 hours of reaction.
[0081] 4. Effect of different initiator dosage on microsphere performance
[0082] The amount of initiator used in the polymerization reaction has a great influence on the reaction rate and degree of polymerization. Too much will lead to too fast polymerization, making it difficult to control the required degree of polymerization. The residual initiator will also affect the product performance. When the amount of initiator is small, the reaction speed is slow, resulting in incomplete polymerization. The shell of the heat-expandable microspheres needs to be as uniform as possible, which requires the reaction to proceed smoothly and the polymerization rate not to be too fast to ensure that the performance of the produced microspheres meets the requirements. We used azobisisobutyronitrile (AIBN) as the initiator (AIBN has a half-life of 10 hours at 59°C) and added a catalyst accounting for 5% of the initiator amount midway to compare the performance of the microspheres prepared with different addition amounts, and determined the optimal feed ratio of the initiator AIBN. The results are shown in Table 5.
[0083] Table 5
[0084] Initiating dose Expansion temperature℃ Shrinkage temperature℃ Steady Bubble Temperature ℃ Foaming ratio 0.6% 125.6 158.7 33 18 0.8% 148.3 172.2 24 23 1.0% 153.8 192.4 39 44 1.2% 158.3 205.7 47 57 1.5% 157.9 213.8 55 65 1.8% 160.4 194.1 34 62 2.0% 162.8 183.5 20 45
[0085] It can be seen from the experiment that when the amount of initiator is too little, the polymerization reaction rate is very slow, the monomer conversion rate is not high, it is difficult for the microsphere shell to accumulate enough polymer, the shell thickness is thin, and the microsphere foaming ratio is low. When the amount of initiator is gradually increased, the monomer conversion rate gradually increases, and the microsphere shell can accumulate enough polymer to maintain the shell to a certain thickness, so that the microsphere can be maintained for a long time after foaming, and the microsphere foaming ratio increases. However, when the amount of initiator is too much, the polymerization rate is too fast, and the polymer precipitates too quickly on the microsphere shell, which makes the uniformity of the microsphere shell worse. At the same time, when the amount of initiator is too much, the average molecular weight of the polymer decreases, which will cause the polymer glass transition temperature to decrease, the microsphere foam stabilization performance to decrease, and ultimately lead to a decrease in the microsphere foaming ratio. Therefore, the amount of initiator should not be too much. 1.0%-1.5% can have a good effect, preferably 1.2-1.5%.
[0086] 5. Effect of different crosslinking agent dosage on microsphere performance
[0087] The experiment directly used trimethylolpropane trimethacrylate (TMPTA) as a crosslinking agent, and tested the heat-expandable microspheres prepared by adding different amounts of the crosslinking agent (relative to the total amount of monomers) to determine the appropriate addition amount. The results are shown in Table 6.
[0088] Table 6
[0089] Amount of crosslinking agent Expansion temperature℃ Shrinkage temperature℃ Steady Bubble Temperature ℃ 1.0% 142.8 175.2 33 1.5% 149.5 185.4 36 2.0% 154.7 197.6 43 2.2% 157.4 206.5 49 2.5% 165.2 212.8 47 2.8% 170.6 215.3 44 3.0% 180.1 221.5 39
[0090] It can be seen from Table 5 that when the amount of cross-linking agent TMPTA added is 2.2%, the microspheres obtained have a lower expansion temperature and a higher foaming ratio. Increasing the total amount of cross-linking agent will significantly increase the expansion temperature and the shrinkage temperature, but the mechanical properties of the capsule wall are affected at high temperatures. The overall continuous temperature is reduced, and the foaming ratio is not as good as before. This is obviously because too much cross-linking agent leads to insufficient plasticity of the shell. Insufficient cross-linking agent will bring the opposite result. Although the reduction of cross-linking agent can make the initial expansion temperature of the microspheres lower, the insufficient mechanical strength of the capsule wall makes it difficult to maintain the foaming process for a long time, the stable foam temperature range is significantly reduced, and the foaming ratio is also affected. Therefore, a cross-linking agent addition amount of 2.0%-2.5% can have a good effect, with 2.2-2.5% being preferred.
[0091] 6. Effect of different homogenization stirring speeds on microsphere performance
[0092] The water / oil was homogenized with different stirring intensities, and then the microsphere products were further reacted to prepare the microsphere products. The particle size and foaming performance of the microspheres were tested to determine the optimal stirring intensity of the homogenization process. The results are shown in Table 7.
[0093] Table 7
[0094] Stirring speed Average particle size (μm) The dispersion is span Foaming ratio 2000rpm 178.21 4.32 26 2500rpm 92.47 2.18 34 3000rpm 46.50 2.03 45 3500rpm 30.85 1.82 51 4000rpm 25.83 1.64 50 4500rpm 19.18 1.71 56 5000rpm 19.45 1.84 60
[0095] From the experimental data, it can be seen that when the stirring speed is low, the particle size of the microspheres is large and there is a phenomenon of adhesion. As the stirring speed increases, the particle size of the microspheres becomes smaller, the dispersion becomes narrower, and the particles become more uniform. However, when the stirring speed is 5000rpm, the particle size and dispersion of the microspheres do not change much, and the temperature of the stirring motor increases significantly during use. Too high a stirring speed has high requirements on the performance of the equipment. Considering comprehensively, it is more appropriate to select 3000-4000rpm for the homogenization process.
[0096] 7. Effect of different polymerization reaction temperatures on microsphere performance
[0097] Appropriate reaction temperature is the main condition for preparing uniform microsphere products. Under the same conditions, the reaction temperature was changed to prepare microsphere products respectively. By testing the performance of the microsphere samples, a more suitable reaction control temperature was screened out. The results are shown in Table 8.
[0098] Table 8
[0099]
[0100] When the reaction is carried out at 50℃ or 62℃, the obtained microspheres have a higher stable foam temperature range, but in comparison, the product prepared at 50℃ has a higher expansion temperature and a lower ratio. This is because at low temperatures, the concentration of AIBN decomposition radicals is low, the polymer molecular weight is higher than at 62℃, and the shell strength is higher. When the reaction temperature is increased to 71℃, the free radical concentration in the system is higher, and the low polymer molecular weight will inevitably reduce the expansion temperature, but it also affects the mechanical strength of the polymer, resulting in poor foaming ratio and stable foam temperature range. At the same time, the higher the temperature, the faster the decomposition rate of AIBN and the faster the polymerization reaction. Too fast a reaction speed makes it difficult for the polymer to precipitate evenly on the surface of the droplet, which may produce microcapsules with uneven capsule wall thickness, which also causes a decrease in thermal expansion performance. Therefore, it is more appropriate to control the reaction temperature at 55-62℃, preferably 60℃.
[0101] 8. Effect of different polymerization reaction pressures on microsphere performance
[0102] The experiment prepared microsphere products by controlling the reaction under different pressure conditions. The performance of the microsphere samples was tested and a more suitable reaction pressure was screened out. The results are shown in Table 9.
[0103] Table 9
[0104] 1 2 3 4 5 6 7 Reaction pressure / MPa 0.28 0.30 0.35 0.40 0.45 0.50 0.55 Foaming ratio 28 45 52 65 74 81 82
[0105] From the change in the foaming ratio of the prepared microspheres, it can be seen that under the same conditions, the greater the pressure, the stronger the foaming ability of the prepared microspheres, but the foaming ability does not change much after the pressure reaches higher than 0.5MPa. Therefore, it is more appropriate to control the reaction pressure at 0.4-0.5MPa, preferably 0.5MPa.
[0106] 9. Performance verification experiment of preparing microspheres by recycling sodium chloride recovered from mother liquor
[0107] In the process of preparing heat-expandable microspheres, the filtered mother liquor contains a large amount of impurities such as NaCl, pigments and a small amount of unreacted raw materials. After adding activated carbon and stirring to adsorb the pigments and impurities and filtering and removing them, the obtained clear filtrate is concentrated under reduced pressure, cooled and crystallized, and filtered to obtain white solid sodium chloride with a purity of more than 99%. The recovered sodium chloride solid is directly used to prepare the water phase material and then used for the preparation of heat-expandable microspheres. By testing the performance of the microspheres, it is determined whether the recovered sodium chloride will affect the product performance. The experiment used the recovered sodium chloride to replace 50%, 80%, and 100% of the industrial sodium chloride for the configuration of the water phase material, and the prepared microspheres have the performance data shown in Table 10.
[0108] Table 10
[0109] Replacement rate of recovered sodium chloride (%) Average particle size (μm) Foaming ratio 50% 28.56 78.45 80% 27.41 80.12 100% 28.95 79.26
[0110] The experimental data show that the use of recycled sodium chloride has no effect on the performance of the microsphere product. In production, the method of using recycled sodium chloride to prepare microspheres can be flexibly selected according to the actual situation. The condensed water collected by the dehydration filtrate is mixed with the washing water and wastewater generated by other channels, and can be further disposed according to the wastewater treatment method of the fine chemical industry.
[0111] Summarize
[0112] Based on the above experiments, for the preparation of heat-expandable microspheres, the water phase and oil phase materials are prepared separately, and then the water phase material, the oil phase material and isobutane (gaseous, foaming agent) are mixed in a closed homogenizer, and a uniform suspension is made through strong stirring. Then, nitrogen is further used to pressurize and heat to carry out polymerization reaction to generate heat-expandable microspheres.
[0113] The aqueous phase material uses deionized water as a carrier and NaCl solution is dissolved in it, the ratio of NaCl to water is 1:3.1 (NaCl accounts for 24.4%), colloidal silica is used as a dispersant, polyvinyl pyrrolidone is used as a co-dispersant, the ratio of the co-dispersant to the dispersant is 1:47 (accounting for 2.0%), the ratio of the inhibitor sodium nitrite to the total amount of monomer is 1:113 (the inhibitor accounts for 0.9%), a small amount of ethanol is used as a flux, and hydrochloric acid is used to adjust the pH value.
[0114] The monomers in the oil phase material are composed of acrylonitrile: methyl methacrylate: methacrylonitrile: methacrylic acid: glycidyl methacrylate = 1:0.6:0.8:0.6. The foaming agent is composed of isopentane: isobutane: isooctane = 1:0.1:0.22 (isobutane gas is directly introduced during the homogenization reaction and is not configured in the oil phase). Azobisisobutyronitrile is used as the initiator, the ratio of initiator to monomer is about 1:76 (the initiator accounts for 1.3%), and the initiator catalyst A accounts for 5% of the catalyst. The ratio of the crosslinking agent (TMPTA) (trimethylolpropane trimethacrylate) to the monomer is about 1:43.5 (the crosslinking agent accounts for 2.3%).
[0115] The oil phase / water phase materials are mixed in a ratio of 1:3.8 (the oil phase accounts for 26%), and then are homogenized at 3000 rpm for 0.5 h, and then transferred to an autoclave for reaction at 120 rpm, 0.5 MPa, and 60° C. When the reaction is halfway through the process (time), an initiator catalyst accounting for 5% of the initiator dose is added through a pressure balance feeder connected to the autoclave, and the reaction is continued until the reaction is completed. The temperature is lowered to below 40° C., and the heat-expandable microsphere product is obtained by filtration, washing, and drying, with a yield of ≥96%.
[0116] The relationship between the key material usage is as follows:
[0117] The ratio of oil phase to water phase is 1:3.8
[0118] Monomer accounts for 15.2% of the total material, and water accounts for 53.5% of the total material
[0119] The ratio of monomer to water is 1:3.45
[0120] The ratio of monomer to blowing agent is 1:0.3169 (blowing agent is 31.7% of monomer)
[0121] The ratio of monomer to dispersant colloidal silica is 1:0.4105 (colloidal silica is 16.4% of the monomer)
[0122] The ratio of monomer to initiator (AIBN) is 1:0.013 (AIBN is 1.3% of the monomer)
[0123] The ratio of initiator (AIBN) to initiator catalyst A is 1:0.05 (initiator catalyst A is 5% of AIBN)
[0124] The ratio of monomer to cross-linking agent (TMPTA) is 1:0.023 (TMPTA is 2.2% of the monomer) and the ratio of monomer to inhibitor sodium nitrite is 1:0.0088 (sodium nitrite is 0.88% of the monomer).
[0125] Although the present invention has selected the preferred embodiments disclosed above, it is not intended to limit the present invention. Any researcher in the field can use the design parameters and contents in the above disclosed embodiments to change and modify the research scheme of the present invention without departing from the spirit and scope of the present invention. Therefore, any simple modification, parameter change and modification made to the above embodiments based on the research essence of the present invention without departing from the content of the present invention, all belong to the protection scope of the present invention.
Claims
1. An application of an initiating catalyst in the preparation of heat-expandable microspheres, characterized in that: The initiating catalyst is composed of one or two inorganic oxides mixed with organic ammonia. The initiating catalyst is uniformly mixed according to the mass ratio of inorganic oxide: organic ammonia of 2-6:
1. When used, 30% ethanol is added at a mass ratio of 1:100 and then completely dissolved before use.
2. Use of an initiating catalyst in the preparation of heat-expandable microspheres as claimed in claim 1, characterized in that: The inorganic oxide is composed of one or two of potassium persulfate, sodium persulfate, ammonium persulfate and hydrogen peroxide, and the organic ammonia is one of ethylenediamine, triethanolamine and monoethanolamine.
3. Use of an initiating catalyst in the preparation of heat-expandable microspheres as claimed in claim 1, characterized in that: The heat-expandable microspheres are prepared by preparing water-phase materials and oil-phase materials, adding initiators, dispersion stabilizers and cross-linking agents, and adopting a suspension polymerization method, including the following steps: (1) preparing aqueous phase materials: in a N2 atmosphere, deionized water, sodium nitrite, polyvinyl pyrrolidone, and sodium chloride are mixed and completely dissolved, and then hydrochloric acid, ethanol, and colloidal silica are added and stirred to uniformly disperse them to obtain a uniform emulsion with a pH value of 5.5-7.0; (2) preparing oil phase materials: in a N2 atmosphere, add acrylonitrile, methyl methacrylate, methacrylonitrile, methacrylic acid, and glycidyl methacrylate monomers into a beaker in sequence, then add a crosslinking agent and an initiator, stir to completely dissolve them, then add a foaming agent, stir to evenly disperse them, and set aside; the process temperature is controlled below 20°C; (3) Homogenization: First, the homogenizer was replaced with N2, and then the prepared water phase material and oil phase material were added into the homogenizer at a volume ratio of 0.79:0.21, and then a foaming agent was added into the homogenizer. The valve was closed and a high-speed stirrer at 3000 rpm was used for homogenization and dispersion. The process temperature was controlled at 5-35°C and the homogenization time was 0.5 hour. (4) Polymerization reaction: first, replace the polymerization reactor with N2, and use nitrogen to pressurize the materials in the homogenizing reactor into the polymerization reactor. After the materials are transferred, continue to pressurize the reactor to 0.5 MPa with nitrogen, close the valve, control the stirring rate at 120 rpm, and gradually increase the temperature to 60° C. within 2 hours. Then, keep the reaction at 60° C. and 0.5 MPa until half of the total reaction time, add an initiator catalyst, continue to react until the reaction is completed, cool to 40° C., release the pressure, and discharge; filter, wash with deionized water, and air dry at 60° C. until the moisture content is less than 2.5%, to obtain a finished product of heat-expandable microspheres; (5) Sodium chloride recovery.
4. Use of an initiating catalyst in the preparation of heat-expandable microspheres as claimed in claim 3, characterized in that: In the step (1), the ratio of ionized water: sodium nitrite: polyvinyl pyrrolidone: sodium chloride: hydrochloric acid: ethanol: colloidal silica is 65-74: 0.15-0.2: 0.15-0.2: 20-25: 0.04-0.08: 1.5-2.5: 7.5-9.0 by mass ratio.
5. Use of an initiating catalyst in the preparation of heat-expandable microspheres as claimed in claim 3, characterized in that: In step (2), the ratio of acrylonitrile: methyl methacrylate: methacrylonitrile: methacrylic acid: glycidyl methacrylate is 1:0.6:0.8:0.6 by mass. The crosslinking agent is trimethylolpropane trimethacrylate, accounting for 2.3% of the total weight of the monomers, and the initiator is azobisisobutyronitrile, accounting for 1.3% of the total weight of the monomers.
Citation Information
Patent Citations
Method for preparing high molecular weight salt-resistant polymer oil displacement agents
CN101747885A
Thermal expansibility microsphere and method for reducing residual monomers therein
CN102775545A
Preparation method and application of dilatation-retarding nano elastic microsphere in-depth profile controlling and oil displacing agent
CN105085799A
Method for preparing thermal expansion microspheres at normal temperature under normal pressure
CN111234293A
Preparation method and application of composite polymeric flocculant
CN116836333A